Morphology of the Filiform Lingual Papillae in Porcupine (Hystrix cristata) - Karan, M.; Yilmaz, S.; Aydin, A. (Wiley-Blackwell, 2011)
The light and scanning electron microscopic structure of the filiform lingual papillae was studied in five adult porcupine (three males and two females). The tongue was characterised by a round tip, a rostral median sulcus and a deep lingual fossa which was situated just rostral to a prominent inter-molar eminence corresponding to a torus linguae. The filiform papillae were curved, enclosed a large connective tissue core and were separated by wide inter-papillary zones covered by a thick epithelium. Most filiform papillae had a cylindrical shape, but the rostral and central parts of the tongue contained a number of flat, comb-shaped papillae with rounded tips.
Keywords: Scanning-Electron-Microscopy; Connective-Tissue; Dorsal Surface; Tongue; Morphogenesis; Light; Rat; Epithelium